Thyrotropin-releasing hormone regulation of human TSHB expression: role of a pituitary-specific transcription factor (Pit-1/GHF-1) and potential interaction with a thyroid hormone-inhibitory element. - Steinfelder, H J (1991)
Regulation of human thyrotropin beta subunit gene (TSHB) expression by thyrotropin-releasing hormone (TRH) was examined in a clonal rat pituitary-cell line (GH3). Transient expression studies were done with various 5'-flanking DNA sequences of TSHB coupled to reporter gene chloramphenicol acetyltransferase. Deletion analysis defined two discrete regions (-128 to -92 base pairs and -28 to +8 base pairs) that each mediated an approximately 2-fold TRH induction. The upstream site contains a DNA sequence with close homology to the DNA-binding site for a pituitary-specific transcriptional factor Pit-1/GHF-1. DNase I footprinting analysis of mouse thyrotropic tumor extract as well as DNA-transfection studies using an expression vector containing an N-terminal deletion of Pit-1/GHF-1 cDNA suggest that Pit-1/GHF-1 or a closely related protein in the thyrotroph mediates TRH responsiveness of this gene. In addition, the downstream site overlaps with the recently characterized thyroid hormone-inhibitory element of TSHB. In fact, deletion of DNA sequences important in thyroid hormone-receptor binding (c-erbAB/c-ERBA2) from +3 to +8 base pairs, significantly reduced (30%) TRH responsiveness. The location of a TRH-stimulatory element near a thyroid hormone-inhibitory element may allow for fine control of TSHB expression in vivo.